MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA PELAJARAN IPS MATERI POKOK INTERAKSI MANUSIA DENGAN LINGKUNGAN KELAS VIIB MTs NEGERI 1 KONAWE SELATAN - Suriatno, Suriatno (Jurnal Penelitian Pendidikan Geografi, 2018)
This is indicated by the average score of each cycle, were cyclence I the average score of the student activity is 2,6, which is sufficient category, increases in cycle II to 3.5 which is in the good category. 2) teacher teaching activity by applying jigsaw type cooperative learning model in each cycle tends to increase. This is indicated by the average score on each cycle, where in cycle I the average score of teacher activity is 2.8 which categorized enough and increased in cycle II to 3.5 that categorized well. 3) learning result of IPS students of class VIIb MTsN Konawe South can be leveledÂ  by applying jigsaw type cooperative learning model on the subject matter of human interaction with its environment, where in cycle I that obtained the lowest value 50, highest score 87, average score 72.4 and mastery studies by 68% who have not reached KKM or from 31 students only 21 people who scored 70. In cycle II obtained the lowestÂ  score of 56 highest score 94, average score 76 and mastery learnig completeness in cycle II has increased from 31 students there are 26 students got the score of 70 with the percentage of learning result completeness is 84%.